2006
DOI: 10.1111/j.1365-2567.2005.02316.x
|View full text |Cite
|
Sign up to set email alerts
|

Dealing with the family: CD147 interactions with cyclophilins

Abstract: SummaryCD147 is a widely expressed plasma membrane protein that has been implicated in a variety of physiological and pathological activities. It is best known for its ability to function as extracellular matrix metalloproteinase inducer (hence the other name for this protein, EMMPRIN), but has also been shown to regulate lymphocyte responsiveness, monocarboxylate transporter expression and spermatogenesis. These functions reflect multiple interacting partners of CD147. Recently, interaction of CD147 with prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
152
1
5

Year Published

2007
2007
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 166 publications
(162 citation statements)
references
References 97 publications
4
152
1
5
Order By: Relevance
“…Therefore, we choose this protein as a potential therapeutic target. Yeast two hybrid studies identified CD147 as an extracellular receptor for cyclophilin and further studies demonstrated that this receptor mediates the pro-inflammatory actions of cyclophilin (16). In our study when we inhibited CD147 we significantly reduced sepsis-induced renal injury.…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…Therefore, we choose this protein as a potential therapeutic target. Yeast two hybrid studies identified CD147 as an extracellular receptor for cyclophilin and further studies demonstrated that this receptor mediates the pro-inflammatory actions of cyclophilin (16). In our study when we inhibited CD147 we significantly reduced sepsis-induced renal injury.…”
Section: Discussionsupporting
confidence: 49%
“…These tissue changes were validated by western blot. Recent studies have demonstrated that extracellular cyclophilin is proinflammatory via the CD147 receptor and that anti-CD147 antibodies are anti-inflammatory (12,13,14,15,16). Administration of anti-CD147 antibodies significantly reduced sepsis-induced acute renal failure and reduced both pro and anti inflammatory cytokine production.…”
Section: Discussionmentioning
confidence: 99%
“…We found that MM284 administration also reduced mRNA expression of a number of proinflammatory mediators downstream from SMAD2 activation, which was also inhibited, suggesting that extracellular cyclophilin plays a role in the inflammation associated with this model of BA. Given that the major signaling receptor for extracellular cyclophilins is CD147 (30), our data suggest that interaction between extracellular cyclophilins and CD147 plays a significant role in inflammation and hepatic pathology in experimental BA. Indeed, several reports have demonstrated activation of the CD147-induced signaling pathways by CypA circulating in extracellular media in a number of inflammatory diseases (31).…”
Section: Discussionmentioning
confidence: 99%
“…It is expressed by many types of cells, including hematopoietic, epithelial, endothelial, and tumor cells. 12,13 It is well documented that Bsg induces MMPs, so it is also known as an extracellular matrix metalloproteinase inducer (EMMPRIN). 14 It is highly up-regulated in many malignant cancer cells and is thought to contribute to cell survival, invasion, metastasis, and multidrug resistance.…”
mentioning
confidence: 99%